Echo the copycat - Holub, Joan; Williams, Suzanne, 1953- (Holub, Joan. Goddess girls, 2016)
In order to fit in at Mount Olympus Academy, new girl and forest-mountain nymph Echo copies the mannerisms of all the other students, but instead of ingratiating herself to her classmates, it only seems to grate on them.